2013
DOI: 10.5271/sjweh.3357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of work-related sustained trapezius muscle activity on the development of neck and shoulder pain among young adults

Abstract: The results indicate that sustained trapezius muscle activity with periods of more than 4 minutes duration for more than half of the working day, increases the rate of neck and shoulder pain in a 2.5-year period. This implicates the importance of reducing the lengths of periods with sustained muscle activity at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 43 publications
(58 reference statements)
1
46
0
2
Order By: Relevance
“…Previous studies in samples of newly-employed workers have shown that repetitiveness, sustained trapezius muscle activity, and high force demands are significant predictors of neck and shoulder pain (11,35,36). Additionally, high and vibrational demands were also associated with upper-/lower-back pain.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies in samples of newly-employed workers have shown that repetitiveness, sustained trapezius muscle activity, and high force demands are significant predictors of neck and shoulder pain (11,35,36). Additionally, high and vibrational demands were also associated with upper-/lower-back pain.…”
Section: Discussionmentioning
confidence: 84%
“…Lin et al [19] found that patients with FSS compensate impaired glenohumeral motion by using accessory musculature. It was established that sustained trapezius muscle activity associated with neck and shoulder pain in healthy young subjects [12].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, the UT is believed to influence pain in the neck. In effect, individuals with neck and shoulder pain display altered trapezius activation patterns, with UT muscle more active than the LT [4] and limited strength or endurance of LT muscle [11,12]. The over-activity of UT will results in scapulothoracic muscle imbalance causing weakness of LT muscle with possible irradiation of the pain downward.…”
Section: Discussionmentioning
confidence: 99%
“…Neck and shoulder disorders are a considerable health problem in the working population with prevalence rates of equal or higher than 30% [4]. Neck pain is common among adults in developed countries and contributes importantly to the demand for medical services and the economic burden of absence from work due to sickness [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation